(untitled) (Revista Iberoamericana de Bioética, 2023)
Face masks have been seen everywhere during the pandemic. They have become its symbol. In some countries, such as Spain, mask requirements have been extended even to outdoors and schools. We have accepted the sacrifice of covering our faces to contain the epidemic, i.e., to save lives. However, when mask requirements were implemented, there seemed to be insufficient evidence to justify them, and the evidence emerging now seems to support the initial objections. In the absence of scientific evidence, an overly intrusive measure such as universal mask-wearing cannot be justified. The emerging evidence needs to be examined thoroughly and honestly, as citizens have the right to know whether the outcome has been worth the sacrifice.